Social Reproduction of Pinisi Boatmakers in Bulukumba Regency, South Sulawesi Province, Indonesia - Mohamad Guntur Nangi; Syamsu A. Kamaruddin; Arlin Adam; Sari Arie Lestari; Titi Saparina (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research explores the process of adaptation and preservation of cultural identity by Pinisi boat builders in Bulukumba district, South Sulawesi, in the face of modern-day dynamics. This research uses a qualitative methodology and a case study approach to explore how this long-standing boatbuilding tradition adapts while maintaining important cultural elements. Results show that boatbuilders blend traditional skills with changing market demands, maintaining cultural symbols such as the 'seven masts of sail' that have functional and symbolic value. The study also highlights the importance of structural support from the government and community that enables boatbuilders to continue their practices in a modern economy. The findings offer valuable insights into how cultural heritage preservation and sustainable economic development can be achieved through adaptive social reproduction processes, underscoring the importance of integrating traditional values with contemporary innovations.